MAKNA RUMAH TINGGAL (LAIKA LANDA) BAGI MASYARAKAT TOLAKI DI DESA SANDARSI JAYA KECAMATAN ANGATA - Harnita Harnita (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2018)
This study aims to find out and describe the meaning of the house (laika landa) for the Tolakinese in Sandarsi Jaya village. Data collection is done through observation, in-depth interviews, and documentation. Data analysis is descriptive qualitative. It obtains from observations and interviews are directly grouped, arranged based on categories and analyzed by the relationship between concepts and reality in there. The results of this study indicate that laika landa is an architectural form of a house that is erected on a pole and is a temporary residence for people who do work as garden/farmer farmers. There are also houses built like laika landa and built in the middle of the village. The house is a permanent residence for the people in Sandarsi Jaya village. Keywords: meaning, laika landa, tolakinese